Donor fraction cell-free DNA and rejection in adult and pediatric heart transplantation - Richmond, Marc E.; Zangwill, Steven D.; Kindel, Steven J.; Deshpande, Shriprasad R.; Schroder, Jacob N.; Bichell, David P.; Knecht, Kenneth R; Mahle, William T.; Wigger, Mark A.; Gaglianello, Nunzio A.; Pahl, Elfriede; Simpson, Pippa M.; et al. (The Journal of heart and lung transplantation, 2020)
Endomyocardial biopsy (EMB) is the current standard for rejection surveillance in heart transplant recipients. The quantification of donor-specific cell-free DNA (cfDNA) may be an appropriate biomarker for non-invasive rejection surveillance. A multicenter prospective blinded study (DNA-Based Transplant Rejection Test, DTRT) investigated the value of donor fraction (DF), defined as the ratio of cfDNA specific to the transplanted organ to the total amount of cfDNA present in a blood sample. A total of 241 heart transplant patients were recruited from 7 centers. Age at transplant ranged from 8 days to 73 years, with 146 subjects <18 years and 95 ≥18 years. All the patients were followed for at least 1 year, with blood samples drawn at routine and for-cause biopsies. A total of 624 biopsy-paired samples were included for analysis through a commercially available cfDNA assay (myTAIHEART, TAI Diagnostics Inc.). A blinded analysis of repeated measures compared the outcomes using receiver operating characteristic (ROC) curves. All primary clinical end-points were monitored at 100%. All analysis and conclusions were reviewed by both an independent external oversight committee and the National Institutes of Health-mandated DTRT steering committee. DF in acute cellular rejection (ACR) 1R/2R (n = 15) was higher than ACR 0R (n = 42) (p = 0.02); DF in antibody-mediated rejection pAMR1 (n = 8) and pAMR2 (n = 12) (p = 0.05) were higher than pAMR0 (n = 466) (p = 0.04 and p = 0.05 respectively). An optimal DF threshold was determined by the use of an ROC analysis, which ruled out the presence of either ACR or antibody-mediated rejection. The cell-free DNA DF holds promise as a non-invasive diagnostic test to rule out acute rejection in both adult and pediatric heart transplant populations.